Intimate partner violence and associated factors among women during the COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis - Alemu, Tewodros Getaneh; Tamir, Tadesse Tarik; Workneh, Belayneh Shetie; Mekonen, Enyew Getaneh; Ali, Mohammed Seid; Zegeye, Alebachew Ferede; Wassie, Mulugeta; Kassie, Alemneh Tadesse; Tekeba, Berhan; Gonete, Almaz Tefera; Techane, Masresha Asmare (Frontiers in Global Women's Health, 2024)
Background During the Coronavirus Disease 2019 (COVID-19) pandemic, intimate partner violence increased globally, but most notably in Africa. Conditions such as movement restrictions, staying home, and school closures increased the risk of domestic violence against women. Intimate partner violence is violence demonstrated by an intimate partner against women including physical, sexual, and psychological violence. Despite existing laws against intimate partner violence in Ethiopia, enforcement by law and the judicial system remains inadequate. Thus, this research aims to identify factors contributing to intimate partner violence among women during the COVID-19 pandemic, drawing insights from the current literature. Method We searched electronic databases, including PubMed, Google Scholar, CINAHL, Cochrane, and others. Two reviewers separately carried out the search, study selection, critical appraisal, and data extraction. A third party was involved in resolving disagreements among the reviewers. All 10 studies included in this study were published in English, with publication dates before 25 February 2024. Articles lacking an abstract and/or full-text, studies that did not identify the intended outcome, and qualitative studies were excluded from the analysis. A Microsoft Excel checklist was used to extract the data, which were then exported to STATA 11. I2, funnel plots, and Egger's test were employed to measure heterogeneity and detect publication bias, respectively. A random-effects model was used to estimate the pooled prevalence of intimate partner violence and associated factors among women during the COVID-19 pandemic. Result The meta-analysis includes a sample size of 6,280 women from 10 articles. The pooled prevalence of intimate partner violence and associated factors among women during the COVID-19 pandemic was found to be 31.60% (95% CI: 21.10–42.11) and significant factors were partner alcohol use with a pooled odds ratio of 1.93 (95% CI: 1.60–2.23), income loss during the COVID-19 pandemic with a pooled odds ratio of 9.86 (95% CI: 6.35–15.70), partner’s literacy level/education status with a pooled odds ratio of 2.03 (95% CI: 1.57–2.63), and decision-making in the household with a pooled odds ratio of 1.82 (95% CI: 1.33–2.50). Conclusion This systematic review and meta-analysis found preliminary evidence that intimate partner violence increased during the COVID-19 pandemic. A partner who has a history of alcohol use, women who had lost income during COVID-19, a partner who has no formal education, and household decisions made by the husband alone were statistically significant factors for intimate partner violence during the COVID-19 pandemic. This implies that the health sector must play a significant role in providing women who are victims of violence with comprehensive healthcare, advocating that violence against women should be viewed as unacceptable, and improving literacy to minimize the consequences of intimate partner violence among women.